Audit Sistem Informasi Layanan Jemput Pajak Online Samsat Kota Tasikmalaya Menggunakan Framework COBIT 4.1 - Hafidz Arrohmat; Nabila Ramadhani Agustina; Tazkira Aulia Azmar; Muhammad Naufal (JOINS (Journal of Information System), 2026)
Digital transformation in the public service sector has encouraged the Tasikmalaya City Samsat to develop the Online Tax Collection Service in order to improve effectiveness, efficiency, and motor vehicle taxpayer compliance. The success of these digital services is influenced by the quality of information technology governance that supports operational activities. This study aims to evaluate the maturity level of information technology governance in the Online Tax Collection Service using the COBIT 4.1 framework. The research methods were conducted through observation, interviews, and questionnaires based on COBIT 4.1 domain indicators. The results showed that the average maturity level score was 2.73, approaching level 3 (Defined Process). The highest gaps were identified in AI6 (Manage Changes) and DS8 (Manage Service Desk and Incidents) because change management and incident handling processes were not formally documented. Based on the gap analysis, several recommendations were proposed, including the preparation of standard operating procedures, improvement of process documentation, implementation of change management, and development of human resource competencies. This study is expected to serve as a reference for improving information technology governance in regional digital tax services.